2015
DOI: 10.1093/jac/dkv346
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenems versus alternative antibiotics for the treatment of bloodstream infections caused byEnterobacter,CitrobacterorSerratiaspecies: a systematic review with meta-analysis

Abstract: Despite limitations of available data, there was no strong evidence to suggest that BLBLIs, quinolones or cefepime were inferior to carbapenems. The reduced risk of mortality observed with quinolone use may reflect less serious illness in patients, rather than superiority over carbapenems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 28 publications
2
40
4
Order By: Relevance
“…Our findings are consistent with those of other recent studies (16)(17)(18). A Spanish study spanning a 16-year time period (1991 to 2006) analyzed 377 episodes of Enterobacter spp.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with those of other recent studies (16)(17)(18). A Spanish study spanning a 16-year time period (1991 to 2006) analyzed 377 episodes of Enterobacter spp.…”
Section: Discussionsupporting
confidence: 93%
“…A 2016 meta-analysis by Harris and colleagues evaluated 11 studies comparing carbapenems with noncarbapenems as treatment for bacteremia from AmpC-producing Enterobacteriaceae (primarily Enterobacter spp.) (18). In an unadjusted analysis, there was no difference in mortality between BLBLIs and carbapenems.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The role of PTZ in the treatment of serious AmpC-E infections is not well established. Tazobactam does not efficiently inhibit the AmpC enzyme, but limited observational data suggest that PTZ has similar effectiveness to carbapenems when AmpC-E test susceptible to PTZ [30,31]. Fluoroquinolones, which are not affected by AmpC enzymes, are another option in treating AmpC-E infections.…”
Section: Ampc β-Lactamase-producing Enterobacteriaceae (Ampc-e)mentioning
confidence: 99%
“…We direct them to a much larger meta-analysis also conducted by Harris et al in 2016 that included 11 studies and revealed no strong evidence to suggest the superiority of carbapenems to other treatment regimens, including ␤-lactamase/␤-lactamase inhibitors, in patients with bloodstream infections due to Enterobacteriaceae with AmpC ␤-lactamases (4). We welcome future studies of the efficacy of non-carbapenemcontaining regimens, such as piperacillin-tazobactam, for the treatment of AmpCharboring Enterobacteriaceae.…”
mentioning
confidence: 99%